Synthesis of non-nucleoside anti-viral cyclopropylcarboxacyl hydrazones and initial anti-HSV-1 structure-activity relationship studies. Issue 24 (15th December 2020) - McNulty, James; Babu Dokuburra, Chanti; D'Aiuto, Leonardo; Demers, Matthew; McClain, Lora; Piazza, Paolo; Williamson, Kelly; Zheng, Wenxiao; Nimgaonkar, Vishwajit L.
Graphical abstract: Abstract: The synthesis of a lead anti-viral cyclopropyl carboxy acyl hydrazone 4F17 (5 ) and three sequential arrays of structural analogues along with the initial assessment and optimization of the antiviral pharmacophore against the herpes simplex virus type 1 (HSV-1) are reported.